Positive electrode material precursor and preparation method thereof, positive electrode material, lithium ion battery and electric equipment
By optimizing the crystal structure of the cathode material precursor, the problem of insufficient cycle performance and capacity of existing cathode materials and lithium-ion batteries is solved, and higher lithium ion transduction efficiency and rate performance are achieved.
Patent Information
- Application Number
- CN202411460449.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-21
AI Technical Summary
The circulation performance and capacity of the cathode materials and lithium-ion batteries prepared by the existing cathode material precursor need to be improved.
Provide an analogical front drive body, in the XRD test, (001) The ratio of grain size of (001) crystal surface and (100) crystal surface is 20-40 °, (001) crystal surface and (101) (101) The semi -peak width ratio of the crystal surface is 0.5 to 1.5. The front -wheel drive is prepared through a co -sedimentation reaction to control the (001) crystal surface and (100) crystal surface of the front -drive body.
By optimizing the crystal structure of the cathode material precursor, the lithium ion transduction efficiency is improved, the cycle performance and capacity of the cathode material are improved, and higher rate performance is achieved.
Smart Images

Figure CN119330427A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, and in particular to a positive electrode material precursor and a preparation method thereof, a positive electrode material, a lithium-ion battery, and an electrical device. Background Art
[0002] Positive electrode materials are important raw materials for preparing lithium-ion batteries, and to a certain extent determine the energy density, power density, cycle performance and production cost of lithium-ion batteries. Existing technologies usually dope positive electrode materials with inactive metals or non-metallic elements to stabilize the bulk phase or sinter and coat the interface to improve electrochemical performance, but not enough attention is paid to the positive electrode material precursors used.
[0003] The preparation method of positive electrode material precursor involves many synthesis parameters and the parameters are coupled with each other, which have an important influence on the performance of the final positive electrode material. For example, the sphericity, internal voids, crystallinity of the precursor, especially the length, thickness and spatial distribution of the primary particles, will be inherited to the positive electrode material or affect the lithiation effect, surface residual alkali and compaction density of the positive electrode material during sintering, further affecting the capacity, rate and cycle of the battery. The cycle performance and capacity of the positive electrode materials and lithium-ion batteries prepared from existing positive electrode material precursors need to be improved. Summary of the invention
[0004] The purpose of the present application is to provide a positive electrode material precursor and a preparation method thereof, a positive electrode material, a lithium-ion battery, and an electrical device, aiming to solve the problem that the cycle performance and capacity of the positive electrode material and lithium-ion battery prepared from the existing positive electrode material precursor need to be improved.
[0005] To achieve the above objectives, the present application provides a positive electrode material precursor, wherein in the XRD test of the positive electrode material precursor, the inverse tangent value arctan[D (001) / D (100) ] is 20-40°, the half-peak width ratio of (001) crystal plane and (101) crystal plane is FWHM 101 / FWHM 001 It is 0.5 to 1.5.
[0006] In some embodiments, the cross-sectional porosity of the positive electrode material precursor is 2% to 15%.
[0007] In some embodiments, the primary particle width-to-length ratio of the positive electrode material precursor is 10% to 35%.
[0008] In some embodiments, the cathode material precursor satisfies at least one of the following conditions:
[0009] A. The median particle size of the positive electrode material precursor satisfies: 1.5 μm ≤ Dv50 ≤20 μm;
[0010] B. The particle size distribution of the cathode material precursor satisfies: 0.2 ≤ (D v90 - D v10 ) / (D v90 + D v10 ) ≤ 0.5;
[0011] C. The specific surface area of the cathode material precursor is 6 - 23 m 2 / g;
[0012] D. The tap density of the cathode material precursor is 1.2 - 2.2 g / cm 3 ;
[0013] E. The looseness of the cathode material precursor is 2.5 - 15;
[0014] F. The sphericity of the cathode material precursor is 85% - 99%;
[0015] G. The core size of the cathode material precursor is 0.5 - 3.0 μm;
[0016] H. The chemical formula of the cathode material precursor is Ni x Co y M (1-x-y) (OH)2, where 0.50 ≤ x ≤ 0.96, 0 < y ≤ 0.20, x + y ≤ 1; M is one or more of Mg, Ti, Zr, Al, Mn, W, Sb, La, Ta, Nb, Ce, Cr, V, Ca, Ba, B.
[0017] This application also provides a method for preparing the above-mentioned cathode material precursor, including:
[0018] Feeding a metal salt solution containing at least nickel and cobalt, a precipitant, and a complexing agent into a reaction kettle with a bottom liquid for coprecipitation reaction to obtain a slurry;
[0019] Separating the solid and liquid of the slurry and drying to obtain the cathode material precursor.
[0020] In some embodiments, at least one of the following conditions is satisfied:
[0021] A. The pH and ammonia concentration in the coprecipitation reaction process satisfy: 1 ≤ [NH3] * lg(pH) ≤ 10, where [NH3] represents the ammonia concentration in the discharged mother liquor, with the unit of g / L, and pH refers to the pH value measured for the slurry at 45°C;
[0022] B. The pH of the coprecipitation reaction is 9.40 - 12.20;
[0023] C. The ammonia concentration of the coprecipitation reaction is 1.0 g / L to 5.5 g / L;
[0024] D. The coprecipitation reaction satisfies: 3≤Q*Me / K*T*V≤18, wherein Q is the amount of the metal salt solution entering the kettle within a period of time (unit L), Me is the total metal ion concentration of the metal salt solution (unit g / L), T is the reaction time (unit h), V is the volume of the slurry (unit L), and K is the ratio of the average relative atomic mass of the metal element in the positive electrode material precursor to the relative molecular mass of the positive electrode material precursor.
[0025] In some embodiments, at least one of the following conditions is met:
[0026] A. The total metal ion concentration of the metal salt solution is 90 g / L to 150 g / L;
[0027] B. The precipitant is a NaOH solution, and the mass percentage concentration of the NaOH solution is 10% to 32%;
[0028] C. The complexing agent is ammonia water, and the mass percentage concentration of the ammonia water is 5% to 21%;
[0029] D. The amount of pure water in the bottom liquid accounts for 20% to 80% of the volume of the reactor;
[0030] E. the pH of the base solution is 11.00-12.20;
[0031] F. The ammonia concentration of the base solution is 1.0 g / L to 10 g / L;
[0032] G. The temperature of the coprecipitation reaction is 40°C to 80°C;
[0033] H. The flow rate of the metal salt solution into the reactor accounts for 1% / h to 12% / h of the reactor volume;
[0034] I. The flow rate of the precipitant into the reactor is 35% / h to 65% / h of the volume of the metal salt solution;
[0035] J. The flow rate of the complexing agent into the reactor is 2.5% / h to 8.5% / h of the volume of the metal salt solution;
[0036] K. The maximum linear velocity of the stirring blade installed in the coprecipitation reaction vessel is 3m / s to 12m / s;
[0037] L. The volume percentage concentration of oxygen in the reactor is 1.0% to 20.5%.
[0038] The present application also provides a positive electrode material, which is prepared from the positive electrode material precursor mentioned above.
[0039] The present application also provides a lithium-ion battery, comprising the above-mentioned positive electrode material.
[0040] The present application also provides an electrical device, comprising the above-mentioned lithium-ion battery.
[0041] Compared with the prior art, the beneficial effects of this application include:
[0042] The inverse tangent value of the ratio of the grain size of the (001) crystal plane and the (100) crystal plane of the positive electrode material precursor provided in the present application is 20-40°. When the positive electrode material is calcined, the lithium ions decomposed by the lithium source tend to be transported in the (001) crystal plane of the precursor. If the precursor hydroxide crystal tends to grow on the 001 crystal plane, a fast and robust Li + Ion diffusion channel improves lithium ion transduction efficiency. In the process of calcining the cathode material precursor of the present application into the cathode material, lithium ions tend to diffuse on the precursor (001) crystal plane and need to diffuse through the (101) crystal plane to the adjacent (001) crystal plane. Therefore, the ratio of the half-peak width of the (001) crystal plane to the (101) crystal plane is 0.5 to 1.5, and the lithium ion diffusion path is short, which is conducive to the improvement of capacity and rate performance.
[0043] The cathode material precursor of the present application controls the preferential growth of the (001) crystal plane and the (100) crystal plane of the precursor, and the relative grain size in the vertical direction between the (001) and (100) crystal planes is appropriate, and the crystallinity of the (101) crystal plane and the (001) crystal plane is moderate, so that the cathode material precursor can better inherit the crystal skeleton of the precursor during the lithiation process, give play to the advantages of the active crystal planes, and improve the cycle performance and capacity.
[0044] The positive electrode material and lithium-ion battery provided by the present application have good cycle performance and high capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0046] Figure 1 This is a surface SEM image of the positive electrode material precursor of Example 1;
[0047] Figure 2 is a cross-sectional SEM image of the positive electrode material precursor of Example 1;
[0048] Figure 3 is the XRD pattern of the cathode material precursor of Example 1;
[0049] Figure 4 This is a surface SEM image of the cathode material precursor of Example 2;
[0050] Figure 5 is a cross-sectional SEM image of the positive electrode material precursor of Example 2;
[0051] Figure 6 is the XRD pattern of the positive electrode material precursor of Example 2;
[0052] Figure 7 This is a surface SEM image of the positive electrode material precursor of Example 3;
[0053] Figure 8 Surface SEM image of the cathode material precursor of Example 4;
[0054] Fig. 9 is a cross-sectional SEM image of the positive electrode material precursor of Example 4;
[0055] Fig.10 is a cross-sectional SEM image of the cathode material precursor of Example 5;
[0056] Fig.11 This is a cross-sectional SEM image of the positive electrode material precursor of Comparative Example 1;
[0057] Fig.12 This is the surface SEM image of the positive electrode material precursor of Comparative Example 2. DETAILED DESCRIPTION
[0058] As used herein:
[0059] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0060] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0061] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0062] In these examples, parts and percentages are by mass unless otherwise indicated.
[0063] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0064] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0065] The present application provides a positive electrode material precursor. In the XRD test of the positive electrode material precursor, the inverse tangent value arctan[D (001) / D (100) ] is 20-40°, the half-peak width ratio of (001) crystal plane and (101) crystal plane is FWHM 101 / FWHM 001 It is 0.5 to 1.5.
[0066] arctan[D (001) / D (100)] For example, it can be 20°, 21°, 22°, 23°, 24°, 25°, 26°, 27°, 28°, 29°, 30°, 31°, 32°, 33°, 34°, 35°, 36°, 37°, 38°, 39°, 40° or any value between 20 and 40°. When the positive electrode material precursor is calcined into a positive electrode material, the lithium ions decomposed by the lithium source tend to be transmitted in the precursor (001) crystal plane. If the precursor hydroxide crystal tends to grow on the 001 crystal plane, a fast and robust Li + Ion diffusion channels improve lithium ion transduction efficiency.
[0067] FWHM 101 / FWHM 001 For example, it can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5 or any value between 0.5 and 1.5. During the calcination of the cathode material precursor into the cathode material, lithium ions tend to diffuse on the precursor (001) crystal plane and need to diffuse to the adjacent (001) crystal plane through the (101) crystal plane. Therefore, the ratio of the half-peak width of the (001) crystal plane to the (101) crystal plane is 0.5 to 1.5, and the lithium ion diffusion path is short, which is conducive to the improvement of capacity and rate performance.
[0068] The inverse tangent value of the ratio of the grain size of the (001) crystal plane and the (100) crystal plane of the positive electrode material precursor provided in the present application is 20 to 40°, and the half-peak width ratio of the (001) crystal plane and the (101) crystal plane is 0.5 to 1.5. By controlling the preferential growth of the (001) crystal plane and the (100) crystal plane of the precursor, the relative grain size in the vertical direction between the (001) crystal plane and the (100) crystal plane is appropriate, and the crystallinity of the (101) crystal plane and the (001) crystal plane is moderate, so that the positive electrode material precursor can better inherit the crystal skeleton of the precursor during the lithiation process, give play to the advantages of the active crystal plane, and improve the cycle performance and capacity.
[0069] In some embodiments, the cross-sectional porosity of the positive electrode material precursor is 2% to 15%, for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or any value between 2% and 15%. The positive electrode material precursor of the present application has a higher porosity, because the electrolyte is easier to wet the surface of the positive electrode material particles and easier to diffuse inside the particles, which is beneficial to lithium ion transmission, and the capacity of the corresponding positive electrode material is higher.
[0070] In some embodiments, the aspect ratio of the primary particles of the positive electrode material precursor is 10% to 35%, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35% or 10% to 35%. The primary particles of the positive electrode material precursor of the present application have a larger aspect ratio, and the precursor composed of thick and short primary particles has a more complete crystal growth and development on the surface of the positive electrode material particles, and the grains are coarser and more uniform. The crack expansion ability caused by internal stress during the charge and discharge cycle is stronger, and the cycle performance is better.
[0071] In some embodiments, the median particle size of the positive electrode material precursor satisfies: 1.5 μm ≤ D v50 ≤20μm, for example, it can be 1.5μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 12μm, 15μm, 17μm, 20μm or any value between 1.5μm and 20μm.
[0072] In some embodiments, the particle size distribution of the positive electrode material precursor satisfies: 0.2≤(D v90 -D v10 ) / (D v90 +D v10 )≤0.5, for example, it can be 0.2, 0.3, 0.4, 0.5 or any value between 0.2 and 0.5.
[0073] In some embodiments, the specific surface area of the cathode material precursor is 6 to 23 m 2 / g, for example, 6m 2 / g, 8m 2 / g, 10m 2 / g, 12m 2 / g, 15m 2 / g, 17m 2 / g, 19m 2 / g, 20m 2 / g, 22m 2 / g, 23m 2 / g or 6~23m 2 Any value between / g.
[0074] In some embodiments, the tap density of the cathode material precursor is 1.2 to 2.2 g / cm 3 , for example, 1.2 g / cm 3 , 1.3g / cm 3 , 1.5g / cm 3, 1.6 g / cm 3 , 1.7 g / cm 3 , 1.9 g / cm 3 , 2.0 g / cm 3 , 2.2 g / cm 3 or any value between 1.2 and 2.2 g / cm 3 Any value therebetween.
[0075] In some embodiments, the looseness of the precursor of the cathode material is 2.5 to 15, for example, it can be 2.5, 4, 5, 7, 9, 10, 11, 13, 14, 15 or any value between 2.5 and 15.
[0076] In some embodiments, the sphericity of the precursor of the cathode material is 85% to 99%, for example, it can be 85%, 87%, 88%, 90%, 92%, 93%, 95%, 97%, 99% or any value between 85% and 99%.
[0077] The precursor of the cathode material of the present application has a narrow particle size distribution, high sphericity, and a small radius of curvature. During the lithium mixing process, the lithium source can adhere more uniformly to the surface, the reaction is more sufficient, and the residual alkali is low; the charge-discharge cycle stress is more uniform, and the particles are not easily cracked.
[0078] In some embodiments, the core size of the precursor of the cathode material is 0.5 to 3.0 μm, for example, it can be 0.5 μm, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm or any value between 0.5 and 3.0 μm.
[0079] In some embodiments, the chemical formula of the precursor of the cathode material is Ni x Co y M (1-x-y) (OH)2, where 0.50 ≤ x ≤ 0.96, 0 < y ≤ 0.20, and x + y ≤ 1; M is one or more of Mg, Ti, Zr, Al, Mn, W, Sb, La, Ta, Nb, Ce, Cr, V, Ca, Ba, B.
[0080] The present application also provides a preparation method of the above-mentioned precursor of the cathode material, including:
[0081] Feeding a metal salt solution containing at least nickel and cobalt, a precipitant, and a complexing agent into a reaction kettle with a bottom liquid for coprecipitation reaction to obtain a slurry;
[0082] Separating the solid and liquid of the slurry and drying it to obtain the precursor of the cathode material.
[0083] Among them, in the co-precipitation reaction, after the reactor is full of materials, the mother liquor is continuously discharged during the reaction process. The amount of mother liquor discharged per hour is the total flow rate of the metal salt solution, the precipitant and the complexing agent entering the reactor.
[0084] In some embodiments, the pH and ammonia concentration of the co-precipitation reaction process satisfy: 1≤[NH3]*lg(pH)≤10, for example, it can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or any value between 1 and 10, wherein [NH3] represents the ammonia concentration in the discharged mother liquor, in g / L, and pH refers to the pH value of the slurry test at 45°C.
[0085] In some embodiments, the pH of the coprecipitation reaction is 9.40-12.20, for example, 9.40, 10.00, 10.50, 11.00, 11.60, 11.90, 12.00, 12.20 or any value between 9.40 and 12.20.
[0086] In some embodiments, the ammonia concentration of the coprecipitation reaction is 1.0 g / L to 5.5 g / L, for example, it can be 1.0 g / L, 2.0 g / L, 3.0 g / L, 4.0 g / L, 5.0 g / L, 5.5 g / L or any value between 1.0 g / L and 5.5 g / L.
[0087] In some embodiments, the coprecipitation reaction satisfies: 3≤Q*Me / K*T*V≤18, for example, it can be 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 or any value between 3 and 18. Wherein, Q is the amount of the metal salt solution entering the kettle within a period of time (unit L), Me is the total metal ion concentration of the metal salt solution (unit g / L), T is the reaction time (unit h), V is the volume of the slurry (unit L), and K is the ratio of the average relative atomic mass of the metal element in the positive electrode material precursor to the relative molecular mass of the positive electrode material precursor.
[0088] Wherein, Q is the amount of metal salt solution entering the kettle within a period of time (unit L), and the period of time can be any period of time in the coprecipitation reaction process, for example, from 0 hours of reaction to 5 hours of reaction, or from 0 hours of reaction to 10 hours of reaction, or from 0 hours of reaction to 15 hours of reaction, or from 0 hours of reaction to 20 hours of reaction, or from 3 hours of reaction to 5 hours of reaction, or from 6 hours of reaction to 9 hours of reaction, or from 10 hours of reaction to 20 hours of reaction, and so on. The amount of metal salt solution entering the kettle is regulated by controlling the flow rate of the metal salt solution.
[0089] Among them, the reaction time T corresponds to the time of the amount Q of metal salt solution entering the kettle within a period of time, for example, the reaction time from reaction 0h to reaction 5h is 5h, the reaction time from reaction 0h to reaction 10h is 10h, the reaction time from reaction 0h to reaction 15h is 15h, the reaction time from reaction 0h to reaction 20h is 20h, the reaction time from reaction 3h to reaction 5h is 2h, the reaction time from reaction 6h to reaction 9h is 3h, the reaction time from reaction 10h to reaction 20h is 10h, and so on.
[0090] The volume V of the slurry refers to the total volume from the start of the reaction to a certain calculated time point. For example, before the mother liquor is discharged, the volume V of the slurry is the total material volume in the reactor at a certain calculated time point. After the mother liquor is discharged, the volume V of the slurry remains basically unchanged and is almost the same as the volume of the reactor.
[0091] Among them, K is the ratio of the average relative atomic mass of the metal element in the positive electrode material precursor to the relative molecular mass of the positive electrode material precursor. The K value will change according to the chemical formula of the positive electrode material precursor.
[0092] In some embodiments, the total metal ion concentration of the metal salt solution is 90 g / L to 150 g / L, for example, it can be 90 g / L, 100 g / L, 110 g / L, 120 g / L, 130 g / L, 140 g / L, 150 g / L or any value between 90 g / L and 150 g / L; the precipitant is NaOH solution, and the mass percentage concentration of the NaOH solution is 10% to 32%; the complexing agent is ammonia water, and the mass percentage concentration of the ammonia water is 5% to 21%.
[0093] In some embodiments, the amount of pure water in the base liquid accounts for 20% to 80% of the volume of the reactor, for example, it can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value between 20% and 80%.
[0094] In some embodiments, the pH of the base solution is 11.00-12.20; the ammonia concentration of the base solution is 1.0 g / L-10.0 g / L, for example, it can be 1.0 g / L, 2.0 g / L, 3.0 g / L, 4.0 g / L, 5.0 g / L, 6.0 g / L, 7.0 g / L, 8.0 g / L, 9.0 g / L, 10.0 g / L or any value between 1.0 and 10.0 g / L.
[0095] In some embodiments, the coprecipitation reaction temperature is 40°C to 80°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or any value between 40 and 80°C.
[0096] In some embodiments, the flow rate of the metal salt solution introduced into the reactor is 1% / h to 12% / h of the volume of the reactor, for example, it can be 1% / h, 3% / h, 5% / h, 8% / h, 10% / h, 12% / h or any value between 1% / h and 12% / h; the flow rate of the precipitant introduced into the reactor is 35% / h to 65% / h of the volume of the metal salt solution, for example, it can be 35% / h, 40% / h, 45% / h, 50% / h, 55% / h, 60% / h, 65% / h or any value between 35% / h and 65% / h; the flow rate of the complexing agent introduced into the reactor is 2.5% / h to 8.5% / h of the volume of the metal salt solution, for example, it can be 2.5% / h, 3% / h, 5% / h, 7% / h, 8.5% / h or any value between 2.5% / h and 8.5% / h.
[0097] In some embodiments, the maximum linear velocity of the stirring paddle installed in the coprecipitation reaction vessel is 3 m / s to 12 m / s, for example, it can be 3 m / s, 5 m / s, 7 m / s, 9 m / s, 10 m / s, 12 m / s or any value between 3 m / s and 12 m / s.
[0098] In some embodiments, the volume percentage concentration of oxygen in the reactor is 1.0% to 20.5%, for example, it can be 1.0%, 3.0%, 5.0%, 7.0%, 8.0%, 10.0%, 11.0%, 13.0%, 15.0%, 18.0%, 20.0% or any value between 1.0% and 20.5%.
[0099] The present application also provides a positive electrode material, which is prepared from the positive electrode material precursor mentioned above.
[0100] The present application also provides a lithium-ion battery, comprising the above-mentioned positive electrode material.
[0101] The present application also provides an electrical device, comprising the above-mentioned lithium-ion battery.
[0102] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0103] Example 1
[0104] This embodiment provides a high-rate nickel-cobalt-based positive electrode material precursor, whose molecular formula is Ni 0.9 Co 0.1 (OH)2, the preparation method thereof is as follows:
[0105] Step 1, preparation of raw material and auxiliary material solution: select soluble sulfate raw material, prepare sulfate solution according to the molar percentage of nickel and cobalt in the molecular formula of 90:10, and the total concentration of transition metal ions nickel and cobalt is 116g / L; the precipitant is NaOH aqueous solution, and its mass percentage concentration is 32wt.%, and the complexing agent is cheap concentrated ammonia water, and its concentration is 21wt.%. The temperature of the prepared sulfate solution is generally maintained at room temperature ~ 50℃, and the liquid alkali and ammonia water can be stored at room temperature.
[0106] Step 2: Condition preparation: Add an appropriate amount of pure water to the reactor as the base liquid. Generally, the volume of pure water can account for 20-80% (vol.%) of the reactor volume. For example, 10 ml 3 The reactor can be added with 2 to 8 m 3 Pure water. This embodiment uses 10m 3 Reactor, pure water 5m 3 As a specific implementation case. Secondly, the reaction temperature is maintained at 60°C, the stirring speed is 165r / min, the corresponding maximum linear speed is 10m / s, and an appropriate amount of nitrogen is introduced into the reactor for protection, and the oxygen concentration in the reactor is required to be lower than 1.5% (vol.%). Finally, an appropriate amount of ammonia water is added to the reactor to maintain the ammonia concentration in the reactor at 2.0-3.0g / L; an appropriate amount of liquid alkali is added to maintain the pH in the reactor at 11.5-12.0.
[0107] Step 3, precipitation reaction: add the prepared sulfate solution, precipitant and complexing agent into the reactor at the same time, adjust the flow rate of NaOH solution, maintain a high pH of 11.5-12.0 for 30 minutes, then control the pH at 10.5-11.0, and maintain the pH value throughout the reaction process; secondly, the ammonia concentration is always maintained at 2.0-3.0g / L, the temperature is 60°C, and the oxygen concentration in the reactor is always lower than 1.5% (vol.%). With the help of a concentration and solidification device, the mother liquor is continuously discharged during the reaction process, and the amount of mother liquor discharged per hour is the total flow rate of sulfate, liquid alkali and ammonia water entering the reactor. The total metal ion concentration of the metal salt solution is Me=116g / L, the reaction time is T (total reaction time is 65h), the volume of the slurry is V (the final volume of the slurry is 10000L), the ratio of the average relative atomic mass of the metal element in the positive electrode material precursor to the relative molecular mass of the positive electrode material precursor is K=0.63, the amount of metal salt solution entering the kettle is Q, and the flow rate of the metal salt solution is adjusted so that the coprecipitation reaction satisfies 7.1≤Q*Me / K*T*V≤7.4; when the particle size reaches 14.6μm, the sulfate solution is stopped.
[0108] Step 4, solid-liquid separation-washing: The slurry obtained in step 3 is subjected to solid-liquid separation and washing by a centrifuge until the pH of the washing liquid is lower than 8.2.
[0109] Step 5, drying-sieving-packaging: The filter cake obtained in step 4 is dried at 120°C, sieved through a 325-mesh sieve, and packaged to obtain the finished product of the positive electrode material precursor of Example 1. The surface SEM image thereof is as follows: Figure 1 As shown, the cross-sectional SEM image is Figure 2 As shown, the XRD pattern is Figure 3 shown.
[0110] Cross-sectional SEM test method: first, the prepared precursor particles are vacuum embedded in the conductive adhesive, then the sample is prepared by ion milling, and finally the sample is photographed by SEM equipment to obtain the final cross-sectional image. The cross-sectional images of other embodiments and comparative examples are obtained by this method.
[0111] Example 2
[0112] The difference between this embodiment and embodiment 1 is that the metal ion molar ratio is adjusted to Ni:Co=96:4, and the parameters of the coprecipitation reaction process must satisfy 11.0≤Q*Me / K*T*V≤11.2; in addition, the ammonia concentration must be maintained at 3.5-5.5 g / L, the pH must be maintained at 10.20-10.55, and the sulfate solution is stopped when the particle size reaches 13.5 μm, so that the corresponding Ni 0.96 Co 0.04 (OH)2 precursor, its surface SEM image is as follows Figure 4 As shown, the cross-sectional SEM image is Figure 5As shown, the XRD pattern is Figure 6 shown.
[0113] Example 3
[0114] The difference between this embodiment and embodiment 1 is that the ratio of the salt solution is adjusted to Ni:Co:Al=93:5:2, the oxygen concentration in the kettle is increased to 4-6%, the ammonia concentration is reduced to 1.5-2.5 g / L, the pH is maintained at 10.70-11.10, and the parameters of the coprecipitation reaction process must satisfy 9≤Q*Me / K*T*V≤11.5; when the particle size reaches 4.8 μm, the sulfate solution is stopped, and the corresponding Ni 0.93 Co 0.05 Al 0.02 (OH)2 precursor, its surface SEM image is as follows Figure 7 shown.
[0115] Example 4
[0116] The difference between this embodiment and embodiment 1 is that the metal ion molar ratio is adjusted to Ni:Co=93:7, and the parameters of the coprecipitation reaction process must satisfy 7.0≤Q*Me / K*T*V≤7.5; in addition, the ammonia concentration must be maintained at 2-3.5 g / L, the pH must be maintained at 10.50-11.00, and the sulfate solution is stopped when the particle size reaches 3.8 μm, so that the corresponding Ni 0.93 Co 0.07 (OH)2 precursor, its surface SEM image is as follows Figure 8 As shown, the cross-sectional SEM image is Fig. 9 shown.
[0117] Example 5
[0118] The difference between this embodiment and embodiment 1 is that the metal ion molar ratio is adjusted to Ni:Co=96:4, the flow rate of each metal salt solution is adjusted, and other conditions are the same as those in embodiment 1. The specific adjustments are as follows: in the first stage (0h~10h), each parameter satisfies 7.1≤Q*Me / K*T*V≤7.4; in the second stage (10h~25h), each parameter satisfies 11.0≤Q*Me / K*T*V≤11.2; in the third stage (25h~end), each parameter satisfies 14.5≤Q*Me / K*T*V≤14.9; when the particle size reaches 13.5μm, the sulfate solution is stopped, and the corresponding Ni 0.96 Co 0.04 The cross-sectional SEM image of (OH)2 precursor is shown in Fig.10 shown.
[0119] Comparative Example 1
[0120] The difference between this comparative example and Example 1 is that the reaction temperature is 35°C, the ammonia concentration is 0-1.0 g / L; each parameter satisfies 20≤Q*Me / K*T*V≤22; when the particle size reaches 15.0 μm, the addition of sulfate solution is stopped, and the corresponding Ni 0.9 Co 0.1 The cross-sectional SEM image of (OH)2 precursor is shown in Fig.11 shown.
[0121] Comparative Example 2
[0122] The difference between this comparative example and Example 4 is that: in the first stage (0h-15h), 5≤Q*Me / K*T*V≤7 is satisfied, and the ammonia concentration is 6.5-8.5g / L; in the second stage (15h-end), 7.5≤Q*Me / K*T*V≤9.5 is satisfied, and the ammonia concentration is 3.5-5.5g / L. When the particle size reaches 4.0μm, the sulfate solution is stopped, and the corresponding Ni 0.93 Co 0.07 (OH)2 precursor, its surface SEM image is as follows Fig.12 shown.
[0123] The physical and chemical parameters of the positive electrode material precursors of various embodiments and comparative examples are shown in Table 1.
[0124] Table 1 Physical and chemical parameters of the positive electrode material precursors of each embodiment and comparative example
[0125]
[0126] Width and length measurement of primary particles: Image J software was used to measure the width and length of primary particles in SEM images with a magnification of 10,000 to 30,000 times. The rule is as follows: the longest dimension of a single primary particle is considered its length, and the dimension measured perpendicular to the longest dimension is considered the width. A sufficient number of data were selected to calculate their average values as the average width and average length of the primary particles.
[0127] Sphericity measurement: Image J software was used to measure the spherical particles in the SEM images with magnifications of 100 to 500 times. The ratio of the longest radius to the shortest radius of each particle was measured*100%, and a sufficient number of data was selected to calculate the average value as the final sphericity.
[0128] Particle size test: The Malvern 2000 laser particle size analyzer, which is the mainstream in the industry, is used as the dispersant, pure water, and ultrasonic dispersion.
[0129] Tap density test: tested using Dandong Better BT-312 / 313 tap density meter.
[0130] Electrochemical performance test
[0131] (1) Preparation of positive electrode material: The nickel-cobalt-based precursors of each embodiment and comparative example were mixed with lithium hydroxide monohydrate at a molar ratio of 1:1.06 in a high-speed mixer and mixed at 1000 rpm for 1 hour. The mixed materials were evenly spread and placed in a sagger and sintered at high temperature in a box furnace. The temperature of the box furnace was set at 500°C in the first stage and maintained for 5 hours; the temperature of the second stage was set at 700-745°C and maintained for 15 hours; the corresponding positive electrode material was obtained by cooling to room temperature with the furnace, crushing, and sieving 325 mesh.
[0132] (2) Button battery electrochemical performance test: The above positive electrode material, conductive carbon black, and binder PVDF (polyvinylidene fluoride) are mixed into a slurry at a ratio of 8:1:1, and evenly coated on aluminum foil to make a positive electrode sheet. The negative electrode sheet uses a metal lithium sheet, and the electrolyte uses 1mol / L LiPF6 EC:DMC:EMC=1:1:1 (volume ratio). In a vacuum glove box, the battery shell, positive and negative electrode sheets, diaphragm and other accessories are assembled into a button battery. The electrochemical performance test was carried out using a blue electric test system, and the charge and discharge cycle test was carried out under 2.7~4.25V conditions, 1C=200mAh·g -1 , test temperature 25±1℃, temperature ≤40%, the results are shown in Table 2.
[0133] Table 2 Electrochemical properties of lithium ion batteries of various embodiments and comparative examples
[0134]
[0135]
[0136] From Example 1 and Comparative Example 1, it can be seen that arctan[D (001) / D (100) ] value is between 20 and 40°, FWHM 101 / FWHM 001 The value is between 0.5 and 1.5, and the positive electrode material obtained by mixing and sintering with lithium salt has better capacity, first efficiency and cycle retention rate. Example 4 and Comparative Example 2 also verify this point, and the cycle performance at 1C is significantly better than that of the comparative example. This is because arctan[D (001) / D (100) ] value can be regarded as the degree of fatness of the grain, and the side surface reflects the degree of preferential growth of the (001) and (100) crystal planes. 101 / FWHM 001 The value reflects the relative crystallinity of the (101) crystal plane. In the lithiation process, it can better inherit the crystal framework of the precursor, give full play to the advantages of the active crystal plane, and improve the material performance.
[0137] When arctan[D (001) / D (100) ] and FWHM 101 / FWHM001 Within a certain range, if the nickel-cobalt-based cross section maintains a certain porosity, it can be seen from Examples 2 and 5 that the sample of Example 5 with a high porosity has a higher capacity. This is because the electrolyte is easier to wet the particle surface and easier to diffuse inside the particle, which is beneficial to lithium ion transmission.
[0138] From Examples 3 and 4, we know that arctan[D (001) / D (100) ] and FWHM 101 / FWHM 001 The difference is not big. Even though Example 3 is doped with Al to stabilize the bulk phase, Example 4, which has a narrow particle size distribution, a higher sphericity, and a larger primary particle aspect ratio, has better cycle performance. The surface crystal growth of the positive electrode material particles obtained from the short primary particle nickel-cobalt-based precursor is more complete, the grains are coarser and more uniform, and the ability to resist crack expansion caused by internal stress during the charge and discharge cycle is stronger.
[0139] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0140] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A cathode material precursor, characterized in that: In the XRD test of the positive electrode material precursor, the inverse tangent value of the ratio of the grain size of the (001) crystal plane to the (100) crystal plane is arctan[D (001) / D (100) ] is 20-40°, the half-peak width ratio of (001) crystal plane and (101) crystal plane is FWHM 101 / FWHM 001 It is 0.5 to 1.
5.
2. The cathode material precursor according to claim 1, characterized in that: The cross-sectional porosity of the positive electrode material precursor is 2% to 15%.
3. The cathode material precursor according to claim 1, characterized in that: The primary particle width-to-length ratio of the positive electrode material precursor is 10% to 35%.
4. The cathode material precursor according to any one of claims 1 to 3, characterized in that: The positive electrode material precursor satisfies at least one of the following conditions: A. The median particle size of the positive electrode material precursor satisfies: 1.5 μm ≤ D v50 ≤20μm; B. The particle size distribution of the positive electrode material precursor satisfies: 0.2≤(D v90 -D v10 ) / (D v90 +D v10 )≤0.5; C. The specific surface area of the positive electrode material precursor is 6 to 23 m 2 / g; D. The tap density of the positive electrode material precursor is 1.2 to 2.2 g / cm 3 ; E. The porosity of the positive electrode material precursor is 2.5 to 15; F. The sphericity of the cathode material precursor is 85% to 99%; G. The core size of the positive electrode material precursor is 0.5 to 3.0 μm; H. The chemical formula of the positive electrode material precursor is Ni x Co y M (1-x-y) (OH)2, where 0.50 ≤ x ≤ 0.96, 0 < y ≤ 0.20, and x + y ≤ 1; M is one or more of Mg, Ti, Zr, Al, Mn, W, Sb, La, Ta, Nb, Ce, Cr, V, Ca, Ba, and B.
5. A method for preparing a cathode material precursor according to any one of claims 1 to 4, characterized in that: include: Passing a metal salt solution including at least nickel and cobalt, a precipitant and a complexing agent into a reaction kettle with a bottom liquid to perform a coprecipitation reaction to obtain a slurry; The slurry is separated into solid and liquid and dried to obtain the positive electrode material precursor.
6. The method for preparing a cathode material precursor according to claim 5, characterized in that: At least one of the following conditions is met: A. The pH and ammonia concentration of the coprecipitation reaction process satisfy: 1≤[NH3]*lg(pH)≤10, wherein [NH3] represents the ammonia concentration in the discharged mother liquor, in g / L, and pH refers to the pH value of the slurry test at 45°C; B. the pH of the coprecipitation reaction is 9.40 to 12.20; C. The ammonia concentration of the coprecipitation reaction is 1.0 g / L to 5.5 g / L; D. The coprecipitation reaction satisfies: 3≤Q*Me / K*T*V≤18, wherein Q is the amount of the metal salt solution entering the kettle within a period of time (unit L), Me is the total metal ion concentration of the metal salt solution (unit g / L), T is the reaction time (unit h), V is the volume of the slurry (unit L), and K is the ratio of the average relative atomic mass of the metal element in the positive electrode material precursor to the relative molecular mass of the positive electrode material precursor.
7. The method for preparing a cathode material precursor according to claim 5, characterized in that: At least one of the following conditions is met: A. The total metal ion concentration of the metal salt solution is 90 g / L to 150 g / L; B. The precipitant is a NaOH solution, and the mass percentage concentration of the NaOH solution is 10% to 32%; C. The complexing agent is ammonia water, and the mass percentage concentration of the ammonia water is 5% to 21%; D. The amount of pure water in the bottom liquid accounts for 20% to 80% of the volume of the reactor; E. the pH of the base solution is 11.00-12.20; F. The ammonia concentration of the base solution is 1.0 g / L to 10 g / L; G. The temperature of the coprecipitation reaction is 40°C to 80°C; H. The flow rate of the metal salt solution into the reactor accounts for 1% / h to 12% / h of the reactor volume; I. The flow rate of the precipitant into the reactor is 35% / h to 65% / h of the volume of the metal salt solution; J. The flow rate of the complexing agent into the reactor is 2.5% / h to 8.5% / h of the volume of the metal salt solution; K. The maximum linear velocity of the stirring blade installed in the coprecipitation reaction vessel is 3m / s to 12m / s; L. The volume percentage concentration of oxygen in the reactor is 1.0% to 20.5%.
8. A positive electrode material, characterized in that Prepared from the positive electrode material precursor according to any one of claims 1 to 4.
9. A lithium ion battery, characterized in that: Comprising the positive electrode material as claimed in claim 8.
10. An electrical device, characterized in that: Includes the lithium ion battery as claimed in claim 9.
Citation Information
Patent Citations
Ternary positive electrode material precursor and preparation method thereof, ternary positive electrode material, lithium ion battery, positive electrode and electric equipment
CN114744164A
Ternary positive electrode active material precursor and preparation method and application thereof
CN117303462A
Positive electrode material precursor with excellent cycle performance, preparation method of positive electrode material precursor, positive electrode material, lithium ion battery and electric equipment
CN117550654A
Doped positive electrode material precursor and preparation method thereof, positive electrode material, battery and power-related equipment
CN117613259A
Lithium-ion battery positive electrode material precursor and preparation method therefor
WO2024197797A1